PERANCANGAN SLEWING ENGINE CRANE KAPASITAS 1 TON SEBAGAI SARANA PENUNJANG BENGKEL MOBIL - Dhika Aditya Purnomo; Bayu W. Karuniawan; Salma Eka Erinda (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Cahaya Abadi Motor Workshop is experiencing problems because they do not have an engine crane that meets their specific needs. Currently, the workshop is forced to rely on manual methods using chains and pulleys when moving machines to be repaired. One of the problems faced is the crane arm that cannot rotate. In this research, a tool design is carried out to help the car workshop. Engine crane with strength, capacity, and dimensions tailored to the conditions of the workshop using Ulrich method. The analysis process will use the FEM (Finite Element Method) approach using FEM-based software. The validity of the simulation results is carried out on the values of the safety factors, von misses stress, and deflection. Analysis of the strength of the overall structure in design concept 1, the actual minimum safety factor value is greater than minimum safety factor requirment (2,178 > 2), and maximum von misses stress is smaller than allowable stress (284,858 Mpa < 310,211 Mpa).